CIRCULATING OVARIAN STEROID PROFILES IN SURTI BUFFALOES SUPEROVULATED WITH FSH AND DIFFERENT DOSES OF PMSG - SAREN, A K; SHAH, R G; KILLEDAR, ANKITA; SARVAIYA, N P; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
Eighteen Surti buffaloes of 2 to 6 lactations were superovulated during breeding season (Augustto February) using FSH and 2 doses of PMSG. Animals were divided into three groups. Group I (n=6)and Group II (n=6) donors were superovulated with single Vm dose of 2500 and 3000 IU PMSG,respectively, on day 10 of the estrous cycle, whereas Group Ill (n=6) donors were treated intramuscularlywith 400 mg FSH per donor in 8 equal doses 12 hours apart for four days. Jugular samples werecollected from all donors at five different stages of MOET, i.e, Day O (Heat), Day 1 O (PMSG treatment),Day 12 (2nd PGF 24 inj. ), Day 14 (Superovulatory estrus) and Day 20 (Flushing} for serum separation. Nosignificant variation was found in serum concentrations of progesterone and estradiol-171! amongthree groups of donors during various stages of MOET. However, the serum concentrations of progesterone and estradiol-17B at various stages of MOET within the group varied significantly (p
Keywords: Buffalo; MOET; Serum progesterone; Estradiol-17bita; Superovulatory response